Uso da rochagem para remineralização de solos de baixa fertilidade - Souza, Wesley dos Santos (2019)
The high price of mineral fertilizers on the market, lead to the need to search for alternative fertilizers that can reduce production costs. Therefore, the present study had as objective to evaluate the efficiency of the use of the rock with the lithotypes volcanic breccia, foiaito, metapiroxenito and metagabronorito of the region of Tuncuduba-CE as remineralizers and correctives of the acidity of two soils of low fertility, in laboratory conditions and vegetation House. In both experiments, two soils (Oxisol Yellow Red Dystrophic and Ultisol Yellow Red Eutrophic) and doses of rock dust originating from the four lithotypes (0, 1, 2 and 4 Mg ha-1) were used, In the experiment, five doses of limestone, corresponding to 0, 25, 50, 75 and 100% of the exchangeable (H+ + Al3+) of each soil were used in this experiment, the rock and limestone powder doses were homogenized with 1 kg of soil, where they remained in sealed plastic bags for a period of 77 days, weekly reading of the pH of each treatment. In the greenhouse only the application of rock powder was carried out and sorghum bicolor was used as an indicator plant. Polyethylene vessels were used with 3 kg of soil homogenized with the doses of rock dust according to each treatment, containing 4 plants per pot. Two cuts were made (50 days after germination and 30 days after the first cut) and the dry matter production of the aerial part was evaluated in each section and quantified macronutrients (P, K, Ca, Mg), micronutrients (Fe, Zn, Cu, Mn), heavy metals (Pb, Cd, Cr and As) and calculated the amount extracted by the plant. All the results were submitted to analysis of variance and the means were compared by the Tukey test at the 5% probability level. The breccias with BVT, FT, GT and MT breccias were not efficient as correctives of soil acidity and nutrient supply K, P, Ca, Fe, Zn and Cu, however they presented potential to be used as source of Mn, being higher in BVT and FT than the other lithotypes. The lithotypes presented low average contents of heavy metals in their constitution and did not influence the accumulation of these elements in the dry matter of the plants.